2019
DOI: 10.1002/hep.30704
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Cholangiocarcinoma on Cyclin D–Dependent Kinase Activity

Abstract: Cholangiocarcinoma (CCA) is a bile duct cancer with a very poor prognosis. Currently, there is no effective pharmacological treatment available for it. We showed that CCA ubiquitously relies on cyclin-dependent kinases 4 and 6 (CDK4/6) activity to proliferate. Primary CCA tissues express high levels of cyclin D1 and the specific marker of CDK4/6 activity, phospho-RB Ser780. Treatment of a 15-CCA cell line collection by pharmacological CDK4/6 inhibitors leads to reduced numbers of cells in the S-phase and senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
(42 reference statements)
1
31
0
Order By: Relevance
“…CDK4/6 amplification and overexpression is reported in breast and other tumors 39 , 40 . A recent study 41 showed dependency of CCA on cyclin D-dependent kinase activity. The analysis of CCA tumor samples employing TCGA database indicated CDK4 and CDK6 overexpression versus normal samples.…”
Section: Discussionmentioning
confidence: 98%
“…CDK4/6 amplification and overexpression is reported in breast and other tumors 39 , 40 . A recent study 41 showed dependency of CCA on cyclin D-dependent kinase activity. The analysis of CCA tumor samples employing TCGA database indicated CDK4 and CDK6 overexpression versus normal samples.…”
Section: Discussionmentioning
confidence: 98%
“…Since nude mice have benefits such as a relatively high engraftment ratios of gastrointestinal tumors, easy observation of subcutaneous tumors, and relatively low price, they remain an important resource for PDX establishment [31,53,62]. The BRJ mice have been used as alternative recipients of cholangiocarcinoma PDX, with a high engraftment ratio (75%) [57,63]. Other solid tumors, such as head and neck tumors, gastric cancers, and bladder cancers, are now under investigation.…”
Section: Establishment Of Pdx Models Using Various Immunocompromismentioning
confidence: 99%
“…Cyclins are known to regulate cell cycle by modulating the activity of cyclindependent kinases (CDKs). Deregulation of the cell cycle through changes in the activity of cell cycle CDKs or their regulators form essential determinants of human cancers [120][121][122][123][124][125][126][127].…”
Section: Cyclinsmentioning
confidence: 99%